Polysulfone Membrane with UV-Photografting Technique and it Application at Soya Milk Filtration Processing - Bambang Piluharto; Achmad Sjaifullah; Istiqomah Rahmawati; Maryanto Maryanto (Jurnal ILMU DASAR, 2013)
In the separation process of solution containing protein, interaction between membrane surface and protein can cause fouling irreversibely. So, efficiency of filtration process will decline. In this research, to improve the effeciency of filtration was done by modification of membrane using UV-photografting technique. Acrylic acid had been introduced topolysulphone membrane via this technique. The hydrophylic membrane was obtained. The membrane performance was evaluated in soymilk fouling test. The first step of research had obtained PSF membrane optimation about PSF 18%. In second step, the research was focused on the modification and characterization of PSF membrane by UV-Fotografting tehchnique. In this technique, monomer concentration and radiation time was used as variable. As the result, PSF membrane had been modificated succesfully by UV- photografting tehchnique with optimum condition in 15 minutes time radiation and concentration of acrylic acid 5%. Performance of modified membranes (flux and permselectivity) were better than unmodified membranes. The fouling test showed that the modified membranes have reduced fouling degree significantly. Keywords : Ultrafiltration membrane, UV-photografting, flux and permselectivity, fouling